Engineering tough, highly compressible, biodegradable hydrogels by tuning the network architecture. Issue 50 (9th June 2017) - Gu, Dunyin; Tan, Shereen; Xu, Chenglong; O'Connor, Andrea J.; Qiao, Greg G.
Abstract : By tailoring the network architecture, tough, highly compressible, biodegradable hydrogels have been developed. This study also shows that the arrangement of each component in the network has a more significant effect on the overall mechanical properties than the network composition. Abstract : By precisely tuning the network architecture, tough, highly compressible hydrogels were engineered. The hydrogels were made by interconnecting high-functionality hydrophobic domains through linear tri-block chains, consisting of soft hydrophilic middle blocks, flanked with flexible hydrophobic blocks. In showing their applicability, the efficient encapsulation and prolonged release of hydrophobic drugs were achieved.